PENGEMBANGAN ALAT PERAGA MATEMATIKA PERKALIAN BAMBU SELIP UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN SISWA KELAS 3 SD - Leonardus Nardi; Suhandi Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research uses Research and Development (R&D) research. This product development refers to the theory of Borg and Gall (1988) including ten stages (Sukmadinata, 2017: 169-170): research and data collection, planning, developing an initial product draft, conducting initial field trials, revising trial results, field testing main product, product revision, wide-scale field trials, final product revision, dissemination and implementation. Research subjects in class III of Kanisius Cungkup Elementary School, Salatiga. The design used for preparing media is the ASSURE model (analyze, state, select, utilize, require, and evaluate). Data was obtained through interview and observation instruments. Data analysis was carried out using descriptive percentage analysis. The research results of the media product